Techniques of network reconfiguration for service restoration in shipboard power system: a review - Dahalan, Wardiah Mohd; Mokhlis, Hazlie (American-Eurasian Network for Scientific Information, Jordan, 2010)
The shipboard power system supplies energy to sophisticated systems for weapons, communications, navigation, and operation. After a fault is encountered, reconfiguration of a shipboard power system becomes a critical activity that is required to either restore service to a lost load or to meet some operational requirements of the ship. Reconfiguration refers to changing the topology of the power system in order to isolate system damage and/or optimize certain characteristics of the system related to power efficiency. When finding the optimal state, it is important to have a method that finds the desired state within a short amount of time, in order to allow fast response for the system. Since the reconfiguration problem is highly nonlinear over a domain of discrete variables, various techniques have been proposed by the researchers. The main tasks of this paper include reviewing the shipboard power system characteristics, studying and reviewing shipboard power system integrated protection, shipboard power distribution systems and typical loads of shipboard power system. A variety of techniques used in previous works have been explained in methodologies review. Many criteria and concepts are used as the basis for consideration in order to achieve the desired objectives.